Вдосконалення напрямів управління грошовими потоками підприємств - Крючко, Леся Станіславівна; Kryuchko, Lesya (Дніпропетровський державний аграрний університет, 2013)
Розглянуто сучасні напрями вдосконалення системи управління грошовими потоками підприємств України, виділено основні недоліки. Запропоновано теоретичні положення щодо оптимізації системи управління грошовими потоками як одного з елементів в оцінці фінансового стану підприємства. Modern directions of perfection of the control system by the monies streams of enterprises of Ukraine are considered in the article, selected the main failings. Theoretical positions are offered in relation to optimization of the control system by monies streams as one of elements in estimation of the financial state of enterprise.
Directions to improve management cash flows of the company
Keywords: управління грошовими потоками; cash flow management; основні недоліки; the main shortcomings; фінансовий стан підприємства; the financial condition of the enterprise